2003
DOI: 10.2337/diacare.26.3.677
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Smoking on Inhaled Insulin

Abstract: OBJECTIVE -This study, one of the first to address issues of pulmonary insulin delivery in smokers, compared pharmacokinetics of inhaled insulin delivered via the AERx insulin Diabetes Management System (iDMS) in nondiabetic cigarette smokers and nonsmokers.RESEARCH DESIGN AND METHODS -In this randomized two-period crossover efficacy and safety trial in 27 nondiabetic smokers and 16 nonsmokers (18 men/25 women, mean age 28 years, mean BMI 23.0 kg/m 2 ), subjects received single doses of inhaled insulin (33.8 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 23 publications
1
52
0
6
Order By: Relevance
“…The study by Himmelman et al (16) used a different insulin inhalation system that utilizes a liquid aerosol formulation, as opposed to the dry-powder formulation in the present study, and also showed a higher AUC-Insulin 0 -360 and C max and a shorter t max for inhaled insulin in smoking subjects. Thus, the effects of smoking on inhaled insulin absorption are not formulation specific.…”
Section: Safety and Tolerabilitymentioning
confidence: 47%
See 1 more Smart Citation
“…The study by Himmelman et al (16) used a different insulin inhalation system that utilizes a liquid aerosol formulation, as opposed to the dry-powder formulation in the present study, and also showed a higher AUC-Insulin 0 -360 and C max and a shorter t max for inhaled insulin in smoking subjects. Thus, the effects of smoking on inhaled insulin absorption are not formulation specific.…”
Section: Safety and Tolerabilitymentioning
confidence: 47%
“…Accordingly, smoking has been shown specifically to increase inhaled insulin absorption in healthy volunteers (13)(14)(15)(16). Therefore, the nicotine-independent effects of tobacco smoke on the lung may have implications for inhaled insulin therapy.…”
mentioning
confidence: 99%
“…Himmelmann and colleagues 71 reported that absorption was faster and peak plasma insulin concentration was greater in smokers, although immediately after smoking, absorption was slower. This study was done in non-diabetic subjects and used low doses of insulin, but it does imply that smoking could affect absorption.…”
Section: The Impact Of Smoking On Inhaled Insulinmentioning
confidence: 99%
“…Active smoking contraindicates its use because of increased bioavailabilty of inhaled insulin, 18,19 while absorption may be retarded in non-smokers exposed to smoke. 20 In patients with type 1 diabetes, there may be problems of dose flexibility: in the present formulation, the minimum unit for dose change is 1 mg, equivalent to 3 units of injected insulin (the 3 mg blister being equivalent to around 8 units).…”
Section: Insulin Without Injectionmentioning
confidence: 99%